A diagnostic conundrum: Is it a periurethral diverticulum/cyst or a bulking agent (Bulkamid)?. Issue 2 (26th October 2022) - Akinjise‐Ferdinand, Oluwaseun; Hubbard, Rachel; Osman, Nadir I.; Chapple, Christopher R.
Abstract: Introduction: Urethral bulking agents are commonly used to manage female stress urinary incontinence (SUI) as they have been suggested to be safe, efficacious, and a minimally invasive surgical option. Bulkamid is a newer bulking agent that has been introduced and promoted in the market for use. It is non‐particulate in nature with high tissue biocompatibility, and consequently, it is difficult to differentiate between Bulkamid and a periurethral cyst on magnetic resonance imaging (MRI). This, therefore, presents a diagnostic dilemma. Methods and Materials: Here we describe two cases with previous injections of Bulkamid referred to our Centre for management of a presumed periurethral diverticulum based on MRI findings. Both patients were reviewed and examined in outpatient clinics with MRI findings discussed at MDT, further imaging was required. Results: We found that a limited noncontrast computed tomography (CT) pelvis, followed by a voiding cystometrogram (VCMG), and then a repeat limited noncontrast CT pelvis effectively differentiated between Bulkamid and these presumed periurethral diverticulae. The theory behind this was that during micturition, the contrast would pass through to the urethral diverticulum and appear as high‐density (bright) material within the periurethral region (the pre‐VCMG was required to prove that any high‐density material was due to the contrast and not pre‐existing high‐contrast material). Conclusion: A CT scan done in conjunction with a VCMG is likely to be more effective in differentiating between Bulkamid and a true periurethral diverticulum than an MRI scan. Appropriate diagnostic evaluation of periurethral lesions can lead to time‐saving and cost‐effective patient management as this will bypass the need for unnecessary investigations and possible unwarranted surgical intervention.